The Role Of Health Promotion in Achieving Household Clean And Healthy Living Behavior (Phbs) With Polling Mothers At UPT Puskesmas Balige - Simangunsong, Lindawati; Rotua Sumihar Sitorus; Monika Helen Sinaga (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The postpartum period is the period that every woman goes through after giving birth. This period lasts from the time the placenta is born until 6 weeks after birth or 42 days after birth. Household Clean and Healthy Living Behavior (PHBS) is carried out to achieve a healthy household. In the household, the primary target must be practicing behavior that can create a PHBS household, which includes giving birth assisted by health workers, giving babies exclusive breast milk, weighing toddlers every month, using clean water, washing hands with clean water and soap, using a toilet. Objectives: to determine the role of health promotion in the achievement of household PHBS with postpartum mothers at the UPT Puskesmas Balige in 2024.Research method: This type of research uses descriptive qualitative.Results: the Clean and Healthy Living Behavior Program (PHBS) for households at the Balige Community Health Center seen from the activity coverage figures. The PHBS program in 2024 has a coverage of (64%) and has not yet reached the target of (70%). In the PHBS program, the household system will be implemented well if all the activity service systems are implemented well and there is a link between the system and the activity implementers and the activity facilities, namely Cadres, Village Midwives and the Community in the household system as well as activity support facilities such as leaflets, posters, flip sheets, booklets and so on provided by the community health center. Apart from that, indicators of the success of the household PHBS program can be seen by the active role of community leaders and community organizations in assessing household PHBS, which can increase the percentage of households implementing PHBS.Conclusion: household PHBS program will be implemented well if all activity service systems are implemented well and there is a link between the system and the activity implementers and activity facilities, namely Cadres, Village Midwives and the Community. It is recommended to enhance coordination and active participation among program managers, village midwives, and the community to ensure the optimal implementation of the PHBS Family Arrangement Program.